Towards thinner and low bowing silicon solar cells: form the boron and aluminum co‐doped back surface field with thinner metallization film. (18th October 2011) - Gu, Xin; Yu, Xuegong; Xu, Jinglin; Fan, Ruixin; Yang, Deren
Abstract : Using thinner wafers can largely reduce the cost of silicon solar cells. One obstacle of using thinner wafers is that few methods can provide good dopant concentration for the back surface field (BSF) and good ohmic contact while generated only in low bowing. In this paper, we have demonstrated the screening–printing B and Al (B/Al) mixture metallization film technique, making use of the screen‐printing technique and the higher solubility of B in silicon to form a B/Al‐BSF. This technique can raise the carrier concentration in the BSF by more than one order of magnitude and reduce the back surface recombination at a low firing temperature (≤800 °C). We have also shown that through the new technique, the metallization paste thickness at the rear could be reduced largely, which however did not degrade the solar cell efficiency. All these efforts are aiming for pushing forward the application of thinner wafers. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : We have demonstrated the screening‐printing B and Al mixture metallization film technique for the aim of pushing forward the application of thinner wafers. This technique can raise the carrier concentration in the back surface field by more than one order of magnitude and minimizing the back surface recombination at a low firing temperature (≤800 °C). Using this technique largely reduce the metallization paste thickness at the rear while not degrading the solar cell efficiency.